Triglyceride/HDL-cholesterol ratio and plasminogen activator inhibitor-1 independently predict high pulse pressure in sickle cell trait and disease. (14th March 2020) - Olabode, Olatunde P.; Akinlade, Olawale M.; Babatunde, Abiola S.; Abdulazeez, Musbau I.; Biliaminu, Sikiru A.; Oyabambi, Adewumi O.; Olatunji, Victoria A.; Soladoye, Ayodele O.; Olatunji, Lawrence A.
Abstract: We hypothesised that TG/HDL-C ratio and PAI-1 would be associated with high pulse pressure (PP) in young adults with sickle cell trait (SCT) and sickle cell disease (SCD). We compared the clinical, biochemical, and cardiometabolic parameters among individuals with normal genotype (HbAA; n  = 60), SCT (HbAS; n  = 60), and SCD (HbSS; n  = 60), all in steady state. Using multivariate linear regression analysis, high PP was positively related to TG/HDL-C ratio in SCT (β = 0.307; p  = .014) and PAI-1 (β = 0.499; p  = .001) in SCD. The curve of receiver operating characteristic also showed that TG/HDL-C ratio and PAI-1 are efficient predictors of high PP in SCT carriers and SCD patients, respectively. This study suggests that increased levels of TG/HDL-C ratio and PAI-1 may be salient risk factors that would promote the development of arterial stiffness and other CVD in SCT carriers and SCD patients.